THE EFFECT OF PROMOTION ON REPURCHASE INTENTION WITH BRAND TRUST AS A MEDIATING VARIABLE(A Study of Evosgoods Product Customers in Denpasar City) - Wiliyanda; Ni Wayan Ekawati (Adisam Publisher, 2026)
The development of promotion through social media marketing encourages companies to better understand the factors influencing repurchase intention. This study aims to analyze the effect of promotion on repurchase intention with brand trust as a mediating variable among customers of Evosgoods products in Denpasar City. This research employs a causal associative quantitative approach using a survey method through online questionnaires distributed to 110 respondents selected using purposive sampling techniques. Data analysis was conducted using path analysis supported by SPSS software.The results indicate that promotion has a positive and significant effect on both brand trust and repurchase intention. Brand trust also has a positive and significant influence on repurchase intention. These findings demonstrate that effective promotional strategies through social media play an important role in strengthening brand trust and encouraging customers’ repurchase intention toward Evosgoods products.